The Yin and Yang of Microglia - Czeh, Melinda; Gressens, Pierre; Kaindl, Angela M. (Developmental neuroscience, 2011)
Microglia, the resident immune cells of the mammalian central nervous system (CNS), play a pivotal role in both physiological and pathological conditions such as the restoration of CNS integrity and the progression of neurodegenerative disorders. Extensive data have been published that describe neuroinflammation by microglial activation to have detrimental consequences on the developing and mature brain. On the other hand, a properly directed and limited inflammatory response is known to be a natural healing process after an insult in several other tissues. Thus, it is not surprising that research results illustrating benefits of neuroinflammation have been emerging over the past decade. Inflammation-mediated benefits for CNS outcomes include mechanisms such as neuroprotection, mobilization of neural precursors for repair, remyelination and axonal regeneration. Here, we review data that highlight the dual aspects of microglia with a focus on the developing brain, i.e. as aggressors potentiating damage and as helpers in the recovery process following CNS damage.